2000
DOI: 10.1021/ol006322p
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Guanidines:  Introducing Diversity in Combinatorial Chemistry

Abstract: The guanidine moiety is an important motif present in many biologically active compounds. Fully substituted guanidines are of key importance for the development of bioactive molecules. The present paper reports on an efficient procedure for the direct solid-phase conversion of amines to fully substituted guanidines under very mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Triethylamine (3 equiv) and commercial available guanidium derivatives (3 equiv) were disssolved in DCM and added to the resin. The mixture was stirred overnight at 25 8C [26].…”
Section: General Proceduresmentioning
confidence: 99%
“…Triethylamine (3 equiv) and commercial available guanidium derivatives (3 equiv) were disssolved in DCM and added to the resin. The mixture was stirred overnight at 25 8C [26].…”
Section: General Proceduresmentioning
confidence: 99%
“…This occurs for N- [116][117][118][119][120][121][122]. NMR studies in the case of HAPyU show that the same structure is found in solution [113,116] (Figure 2.9).…”
Section: Peptide-bond Formation From Aminium/uronium Salt-mediated Rementioning
confidence: 62%
“…Next, we examined distinct substitutions of the guanidine group in the Arg side chain. Analogues of 15 a with electron-withdrawing groups such as aromatic sulfonyl groups (in [16][17][18], or nitrated 19, as well as compounds with tetraalkylated guanidines 20-24 were synthesized. Electron-deficient guanidine compounds 16-19, including the one that was only nitrated (compound 19), showed similar activity to that of 15 a ( Table 2).…”
Section: Resultsmentioning
confidence: 99%